Unwarranted Variation in the Quality of Care for Patients With Diseases of the Thoracic Aorta. Issue 3 (14th March 2017) - Bottle, Alex; Mariscalco, Giovanni; Shaw, Matthew A.; Benedetto, Umberto; Saratzis, Athanasios; Mariani, Silvia; Bashir, Mohamad; Aylin, Paul; Jenkins, David; Oo, Aung Y.; Murphy, Gavin J.; ,
Abstract : Background: Thoracic aortic disease has a high mortality. We sought to establish the contribution of unwarranted variation in care to regional differences in outcomes observed in patients with thoracic aortic disease in England. Methods and Results: Data from the Hospital Episode Statistics (HES) and the National Adult Cardiac Surgery Audit (NACSA) were extracted. A parallel systematic review/meta‐analysis through December 2015, and structure and process questionnaire of English cardiac surgery units were also accomplished. Treatment and mortality rates were investigated. A total of 24 548 adult patients in the HES study, 8058 in the NACSA study, and 103 543 from a total of 33 studies in the systematic review were obtained. Treatment rates for thoracic aortic disease within 6 months of index admission ranged from 7.6% to 31.5% between English counties. Risk‐adjusted 6‐month mortality in untreated patients ranged from 19.4% to 36.3%. Regional variation persisted after adjustment for disease or patient factors. Regional cardiac units with higher case volumes treated more‐complex patients and had significantly lower risk‐adjusted mortality relative to low‐volume units. The results of the systematic review indicated that the delivery of care by multidisciplinary teams in high‐volume units resulted in better outcomes. The observational analyses and the online survey indicated that this is not how services are configured in most units in England. Conclusions: Changes in the organization of services that address unwarranted variation in the provision of care for patients with thoracic aortic disease in England may result in more‐equitable access to treatment and improved outcomes.